Rapid conformational changes of cytochrome P-450: Effect of dimyristoyl lecithin - Tsong, Tian Yow (1978)
Binding of benzphetamine to purified microsomal cytochrome P-450 from rat liver causes a shift in the heme spin state of the protein to favor the high-spin form. This shift is strongly temperature dependent. A rapid temperature jump of a cytochrome P-450/ε benzphetamine mixture, monitored by changes in the Soret absorptions of the heme, reveals two relaxation processes: one in a 50-msec time range (τ(f)) and the other in a 0.3-sec time range (τ(s)). Both relaxations reflect conformational changes of the protein after the substrate binding. No bimolecular reaction of benzphetamine and the enzyme has been resolved. This indicates that there is no absorption change of the heme associated with the initial binding. In the presence of dimyristoyl lecithin, at 25°C τ(f) decreases by nearly one order of magnitude whereas τ(s) decreases to one-third. The enhancement of rates by added phospholipid is both temperature- and concentration-dependent: rates are accelerated only above the gel-liquid crystalline transition temperature, and this effect saturates near the enzyme/lipid ratio of 1:20. In contrast, the lipid does not have significant effect on the equilibrium binding curve of the substrate. These results suggest that the lipid may form an envelope around the enzyme and, depending on its crystalline state, regulates the rate of the substrate-induced conformational changes of cytochrome P-450.